PENGARUH GREEN ACCOUNTING DAN CORPORATE SOSCIAL RERSPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Rr Yoppy Palupi Purbaningsih (Faculty of Economics and Business, 2024)
Three guiding principle economic, social, and environmental development are the center of sustainable development. A corporation must consider the three profit, people, and planet if it hopes to remain sustainable. The inference is that businesses become sustainable through the application of CSR (Corporate Social Responsibility) initiatives as a means of fulfilling a duty to improve society and the environment through the company's production activities, specifically through the application of green accounting in the financial reporting domain. The purpose of this study was to examine and evaluate how corporate social responsibility and green accounting affect company value, which is influenced by profitability. This study looks at 15 manufacturing companies that are listed on the Indonesia Stock Exchange. Purposive sampling was used to gather the research sample, and moderate regression analysis was used to analyze the data. The study's findings indicate that while corporate social responsibility has a major impact on a company's value, green accounting has no such effect. The value of a corporation is influenced by profitability. While corporate social responsibility can reduce the impact of green accounting on a company's value, profitability cannot moderate the impact of green accounting on that value. This study's shortcoming is that it only looks at manufacturing enterprises. In order to determine whether the company has complied with environmental laws, stakeholders, the government, and readers of financial reports interested in purchasing shares from the company are the target audience for this research's contribution. Keywords: Green Accounting, Corporate Social Responsibility, Company Value and Profitability